2021
DOI: 10.1021/acsagscitech.1c00129
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and Properties of an Oil-in-Water Nanoemulsion Loaded with a Terpene-Enriched Oil Mixture Obtained Biotechnologically

Abstract: Biotechnological production is an economical and sustainable pathway to produce some natural terpenes of major industrial importance such as limonene (LIM) and α-terpineol (α-TOH). Thus, in this article, the raw and nonpurified product obtained from the LIM biotransformation (mixture of soybean oil, LIM, and α-TOH), namely as a biotransformation product (BP), was encapsulated into nanoemulsion (NEs) using Quillaja saponins as a natural small-molecule surfactant. Since the long-term physicochemical stability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Therefore, the increasing storage temperature causes LM to move out from the disperse phase and undergo greater oxidation. Although both emulsions stored at 5 °C and 25 °C had similar droplet sizes ( Figure 3 a and Figure 4 a), however, it was found that LM losses were higher at 25 °C than at 5 °C, probably due to the volatilization as well as oxidation of the compound [ 17 , 35 , 36 ]. The results revealed outstanding chemical stability of the LM-loaded emulsions indicating a suitable emulsification method for LM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the increasing storage temperature causes LM to move out from the disperse phase and undergo greater oxidation. Although both emulsions stored at 5 °C and 25 °C had similar droplet sizes ( Figure 3 a and Figure 4 a), however, it was found that LM losses were higher at 25 °C than at 5 °C, probably due to the volatilization as well as oxidation of the compound [ 17 , 35 , 36 ]. The results revealed outstanding chemical stability of the LM-loaded emulsions indicating a suitable emulsification method for LM.…”
Section: Resultsmentioning
confidence: 99%
“…The i-PeakFinder algorithm was used to do automatic peak integration. The sample preparation procedure was adapted from [ 17 ]. LM retention was calculated utilizing the following equation: where, L 0 and L t are the concentrations of LM in emulsions after emulsification and each interval time (5 days), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Formulated eucalyptus NEms showed a very high EE, stability, and a sustained release of emamectin benzoate. Felipe et al formulated a stable NEm of biotransformation product (mixture of soybean oil, limonene, and α-terpineol) using saponins as surfactants. NEms were found stable at 5 and 25 °C for 280 days, and no change in terpineol and limonene was reported for 70 days.…”
Section: Different Nanocarriers Employed For the Encapsulation Of Eosmentioning
confidence: 99%